Combining quantitative, qualitatif and participatory research methods in assessment of the prospects for community-based tsetse control in Busia District, Kenya - Kamara, D.W.; Swallow, B.M.; Echessah, P.N.; Curry, J.J. (OAU/STRC, 1995)
While several traps and targets have been developed to suppress the tsetse flies (Glossina spp.) that transmit trypanosomiasis there have been few examples of self-sustaining `community-based' tsetse control programmes using these devices. The prospects for community-based tsetse control is being assessed in Busia District. Kenya: an area in which both humans and livestock are at risk of contracting trypanosomiasis. This paper describes the combination of quantitative, qualitative and participatory methods that are being used in that assessment and some of the results that have been achieved to date.